PELATIHAN DIGITALISASI MARKETING UNTUK PELAKU USAHA MIKRO (PENDAMPINGAN UMKM SURABAYA) - Saleh, Rahmat; Kwan, Melinda Christanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
Packaging is key for a product to sell and add value. Therefore, MSMEs need to innovate, especially in packaging, such as changing the design, materials, and colors. The purpose of this activity is to enable lecturers and students to carry out one of the Tridharma of Higher Education, namely community service. It can provide facilities to the community on how to innovate in packaging. It is hoped that through this activity, participants, especially MSMEs, can apply innovation to their product packaging, so they can reach a wider market and compete globally. If the product packaging design is attractive, it will support the product to sell better. This can enable MSMEs to gain greater profits. The target of this community service activity is aimed at MSMEs in Surabaya to provide knowledge in innovating design on product packaging. In addition, in this service activity, MSMEs are also provided with knowledge and ways to conduct digital marketing to support their business activities.